p-Sulfonatocalix[4]arene-pyrrolidinium complexation in building multicomponent layered arrays - Ling, I.; Alias, Y.; Sobolev, A.N.; Raston, C.L. (American Chemical Society, 2010)
p-Sulforiatocalix[4]arene and monophosphonium ions, in the presence of N-butyl-N-methylpyrrolidinium ions and aquated lanthanide ions, assemble into bilayers comprised of calixarenes with the phosphonium cations embedded between them; pyrrolidinium ions reside in the calixarene cavities which are normal to the bilayer plane. Replacing the phosphonium cations with bis-phosphonium ions results in the same interplay of the calixarene and pyrrolidinium cations, but with the formation of a different layered structure, which is now devoid of lanthanide ions, unlike the other bilayers, with all the sulfonate groups of the calixarenes residing in a plane with adjacent calixarenes in alternating directions. In aqueous solutions, it 1:1 supermolecule of the calixarene and pyrrolidinium ion is evident in aqueous solution using (1)H NMR spectroscopy.